2018
DOI: 10.1088/1361-6463/aaa2af
|View full text |Cite
|
Sign up to set email alerts
|

Film bulk acoustic formaldehyde sensor with layer-by-layer assembled carbon nanotubes/polyethyleneimine multilayers

Abstract: Trace formaldehyde vapor was detected by a micron-scale AlN film bulk acoustic resonator based on mass-sensitive mechanism. The layer-by-layer carbon nanotubes/polyethyleneimine multilayers were assembled on the resonator surface as the sensitive coating. An almost linear decrease of the resonant frequency was observed as a function of the number of nanotubes/ polyethyleneimine periods. The multilayers showed a random and porous structure and thus provided a large specific surface area for gas adsorption and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…It has been shown that polymer coatings can decrease the quality factor of acoustic resonators, which leads to less sensitive measurements. 41,42 The mechanical properties of some sensitizers, in particular, polymers or polymer composites, can also change due to humidity or analyte adsorption, which can change the sensitivity of the device. 43−45 Aging and humidity of sensitizers like self-assembled monolayers also can affect the sensors' function.…”
Section: ■ General Approachmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that polymer coatings can decrease the quality factor of acoustic resonators, which leads to less sensitive measurements. 41,42 The mechanical properties of some sensitizers, in particular, polymers or polymer composites, can also change due to humidity or analyte adsorption, which can change the sensitivity of the device. 43−45 Aging and humidity of sensitizers like self-assembled monolayers also can affect the sensors' function.…”
Section: ■ General Approachmentioning
confidence: 99%
“…For example, the integration of CNTs inside polymers mitigates the toxicity resulting from inhalation of CNTs, while the CNTs can provide sensitivity the pure polymer cannot match. 175 42 The PEI/MWCNT coating is shown to be selective for formaldehyde against other VOCs, and the sensing response shows little degradation due to humidity. Sayago et al used other polymers (PECH and PEUT) with multiple percentages of MWCNTs incorporated to selectively detect toluene and octane, and to improve both the limit of detection and the sensitivity of the device in comparison to the pure polymer films.…”
Section: ■ Mass Sensorsmentioning
confidence: 99%
See 3 more Smart Citations